2016
DOI: 10.3390/s16040471
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Field-Circuit FEM Modeling and Channel Gain Estimation for Galvanic Coupling Real IBC Measurements

Abstract: Existing research on human channel modeling of galvanic coupling intra-body communication (IBC) is primarily focused on the human body itself. Although galvanic coupling IBC is less disturbed by external influences during signal transmission, there are inevitable factors in real measurement scenarios such as the parasitic impedance of electrodes, impedance matching of the transceiver, etc. which might lead to deviations between the human model and the in vivo measurements. This paper proposes a field-circuit f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…It was also found that attenuation is dependent on the transverse length between electrodes of the same pair, obtaining better levels of received signal by considering longer interelectrode distances. Similar computational models have later been proposed to analyze the effect of the parasitic return path [131], the influence of environmental noise [133] and real experimental conditions [134], the differences between surface-to-surface and implanted communications [130], and the use of noncontact electrodes at the transmitter [131]. A hybrid model considering both electrostatic circuit analysis and FEM model simulations has been proposed in [50] by Park et al to analyze different parameters of HBC channel such as the external coupling characteristics between the environment and the electrodes as well as the transmission performance obtained with different experimental setups comprising VNAs and miniaturized batterypowered wearable transceivers.…”
Section: Body Channel Electric Circuit Modelsmentioning
confidence: 99%
“…It was also found that attenuation is dependent on the transverse length between electrodes of the same pair, obtaining better levels of received signal by considering longer interelectrode distances. Similar computational models have later been proposed to analyze the effect of the parasitic return path [131], the influence of environmental noise [133] and real experimental conditions [134], the differences between surface-to-surface and implanted communications [130], and the use of noncontact electrodes at the transmitter [131]. A hybrid model considering both electrostatic circuit analysis and FEM model simulations has been proposed in [50] by Park et al to analyze different parameters of HBC channel such as the external coupling characteristics between the environment and the electrodes as well as the transmission performance obtained with different experimental setups comprising VNAs and miniaturized batterypowered wearable transceivers.…”
Section: Body Channel Electric Circuit Modelsmentioning
confidence: 99%
“…Body Area Network (BAN) attempts to provide a suitable wireless protocol with low power consumption, high reliability, and lower emissions to collect the information from wearable sensors to evaluate the human health status anytime and anywhere. Unlike common wireless technology, intrabody communication (IBC) uses human tissue as a transmission medium [1,2], so it has the advantages of less path loss, high confidentiality, and high efficiency [3]. Because of this, it has become a potential communication technology for BAN that is standardized in IEEE 802.15.6 [4].…”
Section: Introductionmentioning
confidence: 99%
“…Recent IBC technology research has focused on physical modeling of human channels [5][6][7], in vivo measurements [3,8], and the implement of transceivers [9][10][11]. Because the human body is the transmitting medium for IBC [12], especially for the galvanic coupling type of IBC, a biological safety evaluation of the effect of the IBC electrical signal on the human body is essential.…”
Section: Introductionmentioning
confidence: 99%
“…Several groups have dedicated to the research of propagation mechanism in galvanic coupling IBC. There are many different calculation methods having been proposed for IBC modeling, such as finite element method (FEM) [6,7], quasi-static field theory model [8], equivalent electrical circuit model [9][10][11][12][13], and Field-Circuit FEM [14,15]. Among them, FEM and circuit model has been most widely used in IBC.…”
Section: Introductionmentioning
confidence: 99%